CONSERVATION AGRICULTURE: Study of soil structure, fertility and plant nutrition as efficiency for agricultural production. - Honório de Aquino, Maria Daniela; Mariano, Nilson; Ferrarezi Junior, Edemar; Honório de Aquino , Daiane (Revista Interface Tecnológica, 2024)
Conservation agriculture is one of the main alternatives to minimize environmental degradation, caused through erroneous methods in the production of national and international crops, conventional forms of planting have caused even more the loss and decrease of natural resources, increase in climatic situations, fauna and flora in Brazil and in the world. For this, it is necessary to understand the basic concepts for an ecological transition that provides information on how to be efficient in agricultural production and in the preservation of all resources. Therefore, the objective of the present work is to present the characteristics, biological structure, micro and macro nutrients of the soil, to understand the adequate supply of ecologically correct fertilization and the influence on plant structure, emphasizing the importance and need of essential nutrients for development and the reproductive phase. In order to optimize agricultural production and soil management, contributing to the preservation of the environment and natural resources.
Keywords: Degradation; Soil Attributes; Handling; Natural resources; Productivity